2018
DOI: 10.1371/journal.pone.0198690
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of GABRB2 polymorphisms and the risk of schizophrenia combined with GWAS data of the Han Chinese population and psychiatric genomics consortium

Abstract: Schizophrenia (SCZ) is a severe psychiatric disorder with evidence of a strong genetic component in the complex etiologies. Some studies indicated that gamma-aminobutyric acid (GABA)A receptor β2 subunit gene (GABRB2) was associated with SCZ. Other studies reported a negative association. Moreover, the results of two previous meta-analyses of GABRB2 with SCZ were inconsistent and the sample sizes were limited. Therefore, an updated meta-analysis combined with genome-wide association study (GWAS) data of the Ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
3
1
Order By: Relevance
“…Although we were not able to confirm the aforementioned genes related to GABAergic signaling, we were able to detect 52 intron variants, among them two insertions, with -log10(p) > 5 on GGA13 (8,084,380 -8,135,739 bp), which affect the GABA-receptor subunit GABRB2 (Additional File 2). For GABRB2 as well strong evidence exists to be a causative gene for schizophrenia [43][44][45][46][47][48][49][50] and it seems to be involved in opioid addiction [51]. Iffland et al [6] found the QTL region on GGA1 also associated with FPD, but we were not able to confirm this in our GWAS based on imputed sequence level genotypes.…”
Section: Discussioncontrasting
confidence: 61%
“…Although we were not able to confirm the aforementioned genes related to GABAergic signaling, we were able to detect 52 intron variants, among them two insertions, with -log10(p) > 5 on GGA13 (8,084,380 -8,135,739 bp), which affect the GABA-receptor subunit GABRB2 (Additional File 2). For GABRB2 as well strong evidence exists to be a causative gene for schizophrenia [43][44][45][46][47][48][49][50] and it seems to be involved in opioid addiction [51]. Iffland et al [6] found the QTL region on GGA1 also associated with FPD, but we were not able to confirm this in our GWAS based on imputed sequence level genotypes.…”
Section: Discussioncontrasting
confidence: 61%
“…Genes such as KCNE5 [ 45 ], SHANK3 [ 46 ], CASQ2 [ 47 ], EDNRA (endothelin receptor type A) [ 48 ], EPHB4 [ 49 ], ALPK3 [ 50 ], WNT11 [ 51 ], IRAK2 [ 52 ], FBN1 [ 53 ], SFRP2 [ 54 ], CLCA2 [ 55 ], NEXN (nexilin F-actin binding protein) [ 56 ], PALLD (palladin, cytoskeletal associated protein) [ 57 ], DAB2 [ 58 ], NRP2 [ 59 ], THBS2 [ 60 ], CSF1R [ 61 ], KCNA2 [ 62 ], CACNA1C [ 63 ], F2R [ 64 ], UCHL1 [ 65 ], CCL18 [ 66 ], ITGB1BP2 [ 67 ] and FMOD (fibromodulin) [ 68 ] were reportedly involved in cardio vascular diseases, but these genes might be key for progression of obesity associated type 2 diabetes mellitus. Hu et al [ 69 ], Liu et al [ 70 ], Eltokhi et al [ 71 ], Cai et al [ 72 ], Pfeiffer et al [ 73 ], Lin et al [ 74 ], Royer-Zemmour et al [ 75 ], Pastor et al [ 76 ], Goodspeed et al [ 77 ], Zhang et al [ 78 ], Rogers et al [ 79 ], Su et al [ 80 ] and Foale et al [ 81 ] reported that NRXN1, CRHR1, SHANK2, PSEN2, CKB (creatine kinase B), CD200R1, SRPX2, PTPRZ1, SLC6A1, GABRB2, KCNA1, ASAH1 and LINGO1 were the genes expressed in progression of neuropsychiatric disorders, but these genes might be involved in advancement of obesity associated type 2 diabetes mellitus. Reports indicate that genes include SPHK2 [ 82 ], NPC1L1 [ 83 ], CNTFR (ciliaryneurotrophic factor receptor) [ 84 ], SLC2A4 [ 85 ], EDA (ectodysplasin A) [ 86 ], TGM2 [ 87 ], GCK (glucokinase) [ 88 ], FASN (fatty acid synthase) [ 89 ], FAP (fibroblast activation protein alpha) [ 90 ], PRNP (prion protein) [ 91 ], LYVE1 [ 92 ], SERPINE1 [ 93 ], TNF (tumor necrosis factor) [ 94 ], FASLG (Fas ligand) [ 95 ...…”
Section: Discussionmentioning
confidence: 99%
“…KCNE5 [45], SHANK3 [46], CASQ2 [47], EDNRA (endothelin receptor type A) [48], EPHB4 [49], ALPK3 [50], WNT11 [51], IRAK2 [52], FBN1 [53], SFRP2 [54], CLCA2 [55], NEXN (nexilin F-actin binding protein) [56], PALLD (palladin, cytoskeletal associated protein) [57], DAB2 [58], NRP2 [59], THBS2 [60], CSF1R [61], KCNA2 [62], CACNA1C [63], F2R [64], UCHL1 [65], CCL18 [66], ITGB1BP2 [67] and FMOD ( bromodulin) [68] were reportedly involved in cardio vascular diseases, but these genes might be key for progression of obesity associated type 2 diabetes mellitus. Hu et al [69], Liu et al [70], Eltokhi et al [71], Cai et al [72], Pfeiffer et al [73], Lin et al [74], Royer-Zemmour et al [75], Pastor et al [76], Goodspeed et al [77], Zhang et al [78], Rogers et al [79], Su et al [80] and Foale et al [81] reported that NRXN1, CRHR1, SHANK2, PSEN2, CKB (creatine kinase B), CD200R1, SRPX2, PTPRZ1, SLC6A1, GABRB2, KCNA1, ASAH1 and LINGO1 were linked with progression of neuropsychiatric disorders, but these genes might be involved in advancement of obesity associated type 2 diabetes mellitus. Reports indicate that SPHK2 [82], NPC1L1 [83], CNTFR (ciliaryneurotrophic factor receptor)…”
Section: Discussionmentioning
confidence: 99%